Epidermal Growth Factor Receptor Targeted Therapy of Squamous Cell Carcinoma of the Head and Neck - Sharafinski, Mark E. (2010)
BACKGROUND: Cumulative evidence implicates the epidermal growth factor receptor (EGFR) as an important therapeutic target in head and neck squamous cell carcinomas (HNSCC). The basis for the lack of correlation between EGFR expression in the HNSCC tumor and clinical responses to EGFR inhibitors is incompletely understood. While a variety of mechanisms likely contribute to the effectiveness of EGFR blockade, this review focuses on the biological implications of known EGFR variations and the role of the immune system in mediating clinical responses to EGFR inhibitors. METHODS: A Medline review of articles published in the last 10 years (1999-Present) on EGFR in HNSCC was performed in combination with preliminary data from our laboratories. RESULTS: Studies published to date suggest no association between the expression of EGFR on HNSCC tumors and clinical responses to EGFR inhibitors. Several mechanisms have been proposed to mediate clinical response to EGFR inhibitors in HNSCC. Cumulative results from our laboratories support the role of several mechanisms, including cellular immune activation and mutated EGFR variants, in contributing to the discrepancy between level of EGFR expression and clinical response to EGFR inhibitors. CONCLUSIONS: The efficacy of EGFR targeted therapies may be mediated, at least in part, by the immune system and the presence of the truncated EGFR variant, EGFRvIII, among other factors. Criteria to identify the subset of patients likely to be responsive to EGFR targeted therapies are needed.